Going Concern Opinion: Faktor Mikro Perusahaan Sub Sektor Transportasi 2019-2023 - Kurniasari, Zenita; Rachmawati, Desiana; Agustin, Alifiya Nur; Kinanti, Chika Amelia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the company's micro factors that influence the acceptance of going concern opinions from independent auditors. This study is a quantitative inferential study. The variables studied are company growth, liquidity, leverage and financial distress as micro factors and going concern opinions from independent auditors. Secondary data used are financial reports and annual reports of transportation sub-sector companies for the period 2019-2023. Data was obtained through the website of PT Bursa Efek Indonesia. The sample used was 12 transportation sub-sector companies with an observation period of 5 years, 60 observation data were obtained. Data analysis used logistic regression with data feasibility tests in the form of Overall model fit and Goodness of fit tests, coefficient of determination, and hypothesis testing using the Wald Test. The results show that company growth and liquidity do not affect going concern opinions with p-values ​​of 0,549 and 0,065. Leverage and financial distress have a effect on going concern opinions with p-values ​​of 0,013 and 0,007. Auditors do not necessarily use company growth and liquidity in providing a going concern audit opinion because bad conditions do not necessarily mean experiencing financial difficulties and it is necessary to look at the financial condition from other ratios. While leverage and financial distress are the company's financial conditions that can be used as indicators of long-term financial difficulties. Leverage and financial distress are among those used by auditors as the basis for providing a going concern audit opinion.